IMPLEMENTASI KURIKULUM MERDEKA PADA PEMBELAJARAN PAI DAN BUDI PEKERTI DALAM MENINGKATKAN BERPIKIR KRITIS SISWA SMAN 1 WARU SIDOARJO - Firdausi, Kharisma Syifanaya; Badriyah, Laila; Masnawati, Eli (ANSIRU PAI : Pengembangan Profesi Guru Pendidikan Agama Islam, 2024)
This research aims to analyze the implementation of the Merdeka Curriculum in Islamic Religious Education and Character learning in improving students' critical thinking skills at SMAN 1 Waru, Sidoarjo. The Independent Curriculum provides teachers with the freedom to develop teaching methods that suit students' needs and characteristics, so that it is hoped that they will be able to improve the quality of learning and student learning outcomes. This research uses a qualitative method with a descriptive approach. Data was obtained through interviews, observation and documentation. The research results show that the implementation of the Merdeka Curriculum at SMAN 1 Waru is effective and has a positive impact on students' critical thinking abilities. More flexible and project-based learning facilitates students to be more active, creative and critical in understanding and applying the concepts of Islamic Religious Education and Character. Apart from that, teachers also play an important role in motivating and guiding students to think critically through discussions, questions and answers, and collaborative activities. The conclusion of this research is that the implementation of the Merdeka Curriculum at SMAN 1 Waru Sidoarjo is effective in improving students' critical thinking skills in the subjects of Islamic Religious Education and Character. This research contributes to the development of learning strategies that can be applied in other schools to achieve better educational goals.